Carbon footprint calculator customized for rice products: Concept and characterization of rice value chains in southeast Asia - Wassmann, Reiner; Van-Hung, Nguyen; Yen, Bui Tan; Gummert, Martin; Nelson, Katherine M.; Gheewala, Shabbir H.; Sander, Bjoern Ole (MDPI, 2021)
In this study, we developed user-friendly software (CF-Rice) for calculating the carbon footprints (CF) of rice products. The approach follows the principles of Life Cycle Assessment while incorporating more flexibility for activities specific to rice production. The graphical user interface provides empirical emission and conversion factors obtained from the literature and from primary research studies of rice value chains. CF-Rice also allows the entering of new values for specific processes or practices. Data outputs distinguish among the contributions of individual stages of the value chain as well as different greenhouse gases (GHG), namely, CH4, N2O and CO2. The new tool was then applied to a scenario assessment of rice production in the regional context of Southeast Asia. The CF baseline of a typical rice value chain in the region accounted for a value of around 2300 g CO2e/kgProd. The CF can be reduced by about 27.4% through water-saving practices alone and can further be reduced up to 37.3% through interventions that increase product recovery rates and, thus, reduce food losses. In contrast, straw incorporation into the soil increased the CF by 26.0%. The tool is well suited for impact assessments of advanced practices and technologies of rice value chains.